Small Business in the Economic System of the Country - Popkov, Valeriy P.; Lepeshkin, Sergei M.; Fokina, Olga V.; Orlova, Daria I.; Altsybeeva, Irina G. (International Review of Management and Marketing, 2016)
The role of small business and entrepreneurship in the conditions of market economy is quite crucial. As experience of the developed countries shows, small and medium business play a very important role in economy, their development influences economic growth, acceleration of the scientific-and-technological progress, saturation of market with goods of required quality, additional work creation, namely, these types of business solve many urgent economic, social and other problems. Business as one of the concrete forms of manifestation of public relations promotes not only to increasing material and spiritual capacity of society, not only creates favorable circumstances for practical realization of skills and talents of each individual, but also leads to nation unity, preservation of its national spirit and national pride. Over the last decade Russia experiences the restoration of business and entrepreneurship as an economic basis of society’s well-being. In the conditions of constructions in our country of market relations the center of economic activity moves to a key element of the whole economy and business being its real basis. Exactly by means of business activity goods necessary for the population are produced and services are conducted in society. Business is the future in Russia, the process of accumulation of a critical mass of economic potential will inevitably lead to “an enterprise bubble”. Keywords: small business, economy, state support, economic system JEL Classifications: E32, M54, J21, J24